Hubungan komunikasi terapeutik perawat dengan kepuasan pasien rawat inap - Suryanto, Syafauzi; Rokhmah, Noor Ariyani; Kurniasih, Yuni (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Therapeutic communication is communication carried out during nursing care or service delivery in a hospital setting. In this context, therapeutic communication plays a crucial role in fostering the therapeutic relationship between nurses and clients, thereby enabling clients to feel satisfied with the services provided by nurses. Patient satisfaction is a crucial indicator for improving hospital services. Purpose: The purpose of this study was to determine the relationship between nurses’ therapeutic communication and inpatient satisfaction. Results: This study employed a quantitative research design using an analytic correlation method with a cross-sectional approach. The sampling technique employed was random sampling, involving a total of 85 respondents from the inpatient wards. Data analysis was performed using the Spearman Rank test. The results showed a significant relationship between nurses’ therapeutic communication and inpatient satisfaction at Yogyakarta Hospital, with a p-value of 0.000, which is smaller than the significance level (α = 0.05), and a correlation coefficient of 0.520, indicating a strong and positive relationship. Conclusion: There is a relationship between nurses’ therapeutic communication and inpatient satisfaction at Yogyakarta Hospital. Keywords: Inpatient Car; Nurses’ Therapeutic Communication; Patient Satisfaction. Pendahuluan: Komunikasi terapeutik adalah komunikasi yang dilakukan selama pemberian perawatan atau pelayanan di lingkungan rumah sakit. Berdasarkan hal ini, komunikasi terapeutik memainkan peran penting dalam membangun hubungan terapeutik antara perawat dan pasien, sehingga memungkinkan pasien merasa puas dengan pelayanan yang diberikan oleh perawat. Tujuan: Untuk mengetahui hubungan komunikasi terapeutik perawat dengan kepuasan pasien rawat inap. Metode: Penelitian ini menggunakan desain penelitian kuantitatif dengan metode deskriptif korelasi analitik dengan pendekatan cross-sectional. Teknik pengambilan sampel menggunakan random sampling dan sampel pada penelitian ini sebanyak 85 responden di ruang rawat inap Rumah Sakit Yogyakarta. Teknik analisis data menggunakan uji Spearman Rank. Hasil: Penelitian ini menunjukkan terdapat hubungan antara komunikasi terapeutik perawat dengan kepuasan pasien rawat inap, p-value = 0.000 yang lebih kecil dari batas signifikansi (α = 0.05) dengan tingkat signifikan 0,520 mengindikasikan bahwa kekuatan hubungan berada pada kategori kuat dan memiliki arah positif. Simpulan: Terdapat hubungan antara komunikasi terapeutik perawat dengan kepuasan pasien rawat inap di Rumah Sakit Yogyakarta. Kata Kunci : Kepuasan Pasien; Komunikasi Terapeutik Perawat; Rawat Inap.